GABAergic Neurons in the Central Region of the Spinal Cord: A Novel Substrate for Sympathetic Inhibition - Deuchars, Susan A. (J Neurosci, 2005)
Homeostatic maintenance of widespread functions is critically dependent on the activity of the sympathetic nervous system. This activity is generated by the CNS acting on the sole output cells in the spinal cord, sympathetic preganglionic neurons (SPNs). SPNs are subject to control from both supraspinal and spinal inputs that exert effects through activation of direct or indirect pathways. A high proportion of indirect control is attributable to activation of spinal interneurons in a number of locations. However, little is known about the different groups of interneurons with respect to their neurochemistry or function. In this study, we report on a novel group of GABAergic interneurons located in the spinal central autonomic area (CAA) that directly inhibit SPN activity. In situ hybridization studies demonstrated a group of neurons that contained mRNA for glutamic acid decarboxylase (GAD)(65) and GAD(67) within the CAA. Combining in situ hybridization with trans-synaptic labeling from the adrenal gland using pseudorabies virus identified presympathetic GABAergic neurons in the CAA. Electrical stimulation of the CAA elicited monosynaptic IPSPs in SPNs located laterally in the intermediolateral cell column. IPSPs were GABAergic, because they reversed at the chloride reversal potential and were blocked by bicuculline. Chemical activation of neurons in the CAA hyperpolarized SPNs, an effect that was also bicuculline sensitive. We conclude that the CAA contains GABAergic interneurons that impinge directly onto SPNs to inhibit their activity and suggest that these newly identified interneurons may play an essential role in the regulation of sympathetic activity and thus homeostasis.